Influence of social capital on the stunting incidence : a cross- sectional study - Setianingsih, Triseu; Suharso, Eddy; Hussain, Nervana (Universitas Padjadjaran, 2024)
ABSTRACT Introduction: The problem of stunting is caused by many factors, including geographical, social, and political problems. The role of social capital has been shown to impact economic development and health in some countries, including the problem of stunting, but has not been widely studied. The purpose of this study is to analyze the effect of social capital on the incidence of stunting in South Cikarang Sub District, Bekasi Regency. Methods: The type of study is observational with a cross-sectional design. The population had 106 neighborhoods as respondents, with simple random sampling technique, and a total sample of 91 people. The research instrument uses a questionnaire whose validity and reliability have been tested. The independent variables studied were 7 variables. Univariate in the form of frequency distribution, Bivariate analysis using chi square followed by logistic regression to obtain a predictive model using SPSS Version 24. Result: 65.9% of neighborhoods have stunting rates in their area. This figure is still above the government's target. Of the 7 variables studied, all of them are related to the incidence of stunting. Suprastructure variables with p=0.001, community participation with p=0.004, community empowerment in development with p=0.001, community control in development and stunting events with a value of p=0.001, motives of empowerment in development with p=0.004, the existence of cadres as agents of change with p=0.001, involvement of various stakeholders with p=0.001. The most dominant factor is the suprastructure of various stakeholders, with p=0.001. The most dominant factor is the t variable, with OR=49.398 at 95% of CI (3.623–673.6). Predictive models are produced so that preventive efforts are expected to reduce the incidence of stunting. Conclusion: The high incidence of stunting in the neighborhood area shows that the social capital of the community still needs to be improved in handling stunting. Community groups in the neighborhoods that have poor suprastructure will be at risk of their area having a stunting incidence.Keywordsocial capital, stunting, incidence